Marketing Otherness: A Re-Orientalist gaze into Pakistani fiction with focus on Trespassing and Typhoon - Saleem, Rohma (Journal of Research in Humanities, 2023)
This paper, drawing upon the works of Graham Huggans’ The Postcolonial Exotic and Lisa Lau’s Re-Orientalism: The Perpetration and Development of Orientalism by Oriental, explores the working of reduced, essentialized and skewed representation in the fictional work of Uzma Aslam Khan Trespassing and Typhoon by Qaisera Shahraz. Both Huggans and Lau have contested against the aggressive promotion of many Oriental writers by Occidental marketing pundits. Both of them are of the opinion that the works that gain recognition in international market and which have a high scope of winning prizes of international acclaim are invariably those which appease the Western thirst for the mysterious and elusive East. These fictional works are usually two pronged. They not only present such images which substantiate Western notion of East being unfathomable. But they cleverly juxtaposed these, with other, more vilifying tropes of East as necessarily backward, steeped in poverty, corruption, conservatism, a natural antithesis of the liberated West. These are some of the fixed images which are repeated with a consistency across the border. Pakistani English fiction writers are also charged with presentation of essentialized and monolithic picture of the country. The present paper, making use of interpretive and explorative analysis, seeks to investigate the workings of these exoticizing strategies in the selected texts of Uzma Aslam Khan Trespassing and Qaisera Shahraz Typhoon